The Portuguese in West Africa, 1415-1670 : a documentary history - Newitt, M. D. D. (Cambridge ; New York : Cambridge University Press, 2010)
"The Portuguese in West Africa, 1415-1670 brings together a collecti on of documents - all in new English translation - that illustrate aspe cts of the encounters between the Portuguese and the peoples of North a nd West Africa in the period from 1400 to 1650. This period witnessed t he diaspora of the Sephardic Jews, the emigration of Portuguese to West Africa and the islands, and the beginnings of the black diaspora assoc iated with the slave trade. The documents show how the Portuguese tried to understand the societies with which they came into contact and to r econcile their experience with the myths and legends inherited from cla ssical and medieval learning. They also show how Africans reacted to th e coming of Europeans, adapting Christian ideas to local beliefs and ma king use of exotic imports and European technologies. The documents als o describe the evolution of the black Portuguese communities in Guinea and the islands, as well as the slave trade and the way that it was org anized, understood, and justified"--
The Portuguese in Morocco -- The early voyages to West Africa -- The Atlantic islands -- The upper Guinea coast and Sierra Leone -- Elmina and Benin -- Discovery of the kingdom of Kongo -- Angola, Paulo Dias an d the founding of Luanda -- The slave trade -- Conflict in the kingdom of Kongo in the 1560s -- Christianity in the Kongo -- The Angolan wars -- People and places.
Includes bibliographical references and index.
Keywords: Portuguese -- Africa, West -- History -- Sources; Slave trade; Africa, West -- Discovery and exploration -- Portuguese -- Sources; Africa, West -- History -- To 1884 -- Sources